2017
DOI: 10.1007/s10689-017-9998-5
|View full text |Cite
|
Sign up to set email alerts
|

TP53 germline and somatic mutations in a patient with fibrolamellar hepatocellular carcinoma

Abstract: Li-Fraumeni syndrome is a rare hereditary cancer predisposition syndrome associated with germline pathogenic variants in TP53 gene. The phenotype may vary from classical to variant forms, known as Li-Fraumeni-like phenotypes. We searched for pathogenic variants in TP53 in a 14 year-old female diagnosed with fibrolamellar hepatocellular carcinoma, a rare subtype of hepatocellular carcinoma. The proband is a heterozygote carrier of the TP53 c.467G>A (p.Arg156His) in exon 5, and her mother is an asymptomatic carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Association with germline pathogenic variants of TP53 gene has been reported suggesting that some cases of fibrolamellar HCC might represent Li-Fraumeni syndrome. Interestingly, in the case described by Andrade et al, a germline mutation of TP53 was identified not only in proband affected by fibrolamellar HCC but also in her asymptomatic mother [54].…”
Section: Pathologymentioning
confidence: 97%
“…Association with germline pathogenic variants of TP53 gene has been reported suggesting that some cases of fibrolamellar HCC might represent Li-Fraumeni syndrome. Interestingly, in the case described by Andrade et al, a germline mutation of TP53 was identified not only in proband affected by fibrolamellar HCC but also in her asymptomatic mother [54].…”
Section: Pathologymentioning
confidence: 97%
“…Such a model was supported by a whole exome sequencing study of 34 tumors from 6 multifocal HCC patients, which mapped commonly mutated genes onto phylogenetic trees [32]. While oncogene-sis is predominately through the accumulation of somatic mutations, conditions such as Li-Fraumeni syndrome, a germline TP53 mutation, can also predispose individuals to HCC development under rare circumstances [33,34]. In pathway (A), a morphologically normal liver is exposed chronically to pro-cirrhotic viruses or toxins.…”
Section: Pathogenesis Of Hepatocellular Carcinomamentioning
confidence: 99%
“…In extension to mutations, TP53 expression is altered by various other factors such as chromosomal abnormalities and viral infections either directly or indirectly. 42 Structural changes in chromosomes resulting in loss or gain of alleles have been detected in few chromosomes in more than 30% of HCCs. While tumor suppressor genes like p53, Rb and other CDKN2A fall in these regularly deleted chromosomal regions 43-45 epigenetic silencing of cancer related genes by unusual DNA methylation pattern also have been reported in HCC while p16 and.…”
Section: Several Genes Are Known To Regulate Hccmentioning
confidence: 99%